Secondary amyloidosis with concomitant gastric GIST and gastric adenocarcinoma - A case report - Ankita Soni; Nishant Batta; Shefali Mehmi; Vikram Narang; Bhavna Garg; Harpreet Kaur (Indian Journal of Pathology and Microbiology)
Secondary amyloidosis is a well-established entity and has been described in association with chronic inflammatory conditions such as rheumatoid arthritis, ankylosing spondylitis, bronchiectasis, tuberculosis, etc., It has also been reported in association with neoplasms such as Hodgkin's lymphoma, Waldenstrom's macroglobulinemia, renal cell carcinoma, lung carcinoma, etc. However, only a few case reports documenting the association of amyloidosis with gastrointestinal tumor (GIST) and gastric adenocarcinoma are available in the literature. Hereby, we report a case of a 74-year-old male who presented with colicky abdominal pain and vomiting. Ultrasonography revealed a common bile duct (CBD) stone and a small extra-luminal gastric mass. Endoscopic retrograde cholangiopancreatography (ERCP) was performed to remove the CBD stone which revealed an incidental finding of gastric ulcer. A biopsy was taken from the gastric ulcer which on histopathological examination was confirmed as adenocarcinoma leading onto total gastrectomy. During total gastrectomy, an inadvertent injury to the spleen led to simultaneous splenectomy. Multiple samples from the gastric ulcer, the extra-luminal gastric mass, and the spleen were subjected to histopathological examination. Gastric ulcer was confirmed as adenocarcinoma, gastric extra-luminal mass was confirmed as GIST, and splenic examination revealed widespread deposition of amyloid which on Congo-red stain imparted an apple-green birefringence on polarizing microscopy. To the best of our knowledge, this is the first-ever case of such an association where gastric adenocarcinoma occurred with concomitant gastric GIST and secondary amyloidosis of the spleen.